Impact of maternal and child dental anxiety on oral health-related quality of life of 5–6-year-old preschool children - Esa, Rashidah (Health Qual Life Outcomes, 2020)
BACKGROUND: There is a lack of evidence with regards to the association between both maternal and child dental anxiety and the mother’s perception of her child’s oral health-related quality of life (COHRQoL). The aim of this study was to investigate the association of maternal and child dental anxiety with COHRQoL and the effect of demographic factors as moderators in this relationship. In addition, the association between child’s dental caries experience and the COHRQoL was also assessed. METHODS: A cross-sectional study was conducted involving 1150, 5–6 year-old preschool children in Selangor, Malaysia. Mothers answered a questionnaire on socio-economic status, the Malay-Modified Dental Anxiety Scale to assess maternal dental anxiety, and the Malay-Early Childhood Oral Health Impact Scale to assess COHRQoL. Child's dental anxiety was assessed using the Malay-Modified Child Dental Anxiety Scale via a face-to-face interview prior to oral examination to assess dental caries. Data were analysed using structural equation modelling to assess the relationship between maternal and child dental anxiety and COHRQoL. RESULTS: Overall, complete data on 842 mother–child dyads were analysed. The mean scores of total ECOHIS, the child impacts section (CIS), and the family impacts section (FIS) were 17.7 (SD = 4.9), 12.6 (SD = 3.7), and 5.1 (SD = 1.9), respectively. The mean dental anxiety scores for mothers and children were 11.8 (SD = 4.5) and 16.9 (SD = 4.3), respectively. Maternal dental anxiety was associated with the CIS (b = 0.08, p < 0.001), the FIS (b = 0.01, p = 0.001), and the total ECOHIS (b = 0.14, p < 0.001). Maternal education level, income, urban/rural location, and kindergarten type were moderators to the relationship. In addition, there was also a significant relationship between child’s dental caries experience and COHRQoL (p < 0.001). CONCLUSIONS: Maternal dental anxiety and child’s dental caries experience have significantly impacted the COHRQoL, the CIS, and the FIS domains. Demographic factors such as maternal education, income, urban/rural location, and kindergarten type acted as moderators that can strengthen or weaken the relationship between maternal dental anxiety and COHRQoL of 5–6-year-old preschool children.